Women's perceived social support: associations with postpartum weight retention, health behaviors and depressive symptoms - Sabrina Faleschini; Lynne Millar; Sheryl L. Rifas-Shiman; Helen Skouteris; Marie-France Hivert; Emily Oken (BMC, 2019)
Abstract Background Social support may promote healthful behaviors that prevent excess weight at critical periods in women's life. Our objective was to investigate associations of social support at 6 months postpartum with women's health behaviors that have previously been shown to predict weight retention at 1 year postpartum. Methods At 6 months postpartum in Project Viva, a pre-birth prospective cohort in Massachusetts, women reported social support using the Turner Support Scale, depressive symptoms using the Edinburgh Postnatal Depression Scale, diet using PrimeScreen, average number of hours walking, light/moderate and vigorous physical activity, television viewing, and sleeping each day. Results Among 1356 women, greater partner support was associated with higher levels of walking (OR 1.36, 95% CI [1.01, 1.82]) and intake of fiber (OR 1.43, 95% CI [1.06, 1.91]) and lower intake of trans-fat (OR 1.49, 95% CI [1.11, 2.01]). Support from family/friends was marginally related to healthful levels of light/moderate physical activity (OR 1.26, 95% CI [0.96, 1.65]) and television viewing (OR 1.29, 95% CI [0.99, 1.69]). Both sources of support were strongly associated with lower odds of incident depression (OR 0.33, 95% CI [0.20, 0.55] and OR 0.49, 95% CI [0.30, 0.79], respectively). We did not find associations with vigorous physical activity or sleep duration. Conclusions Social support is important to the physical and mental health of new mothers and may promote behaviors that limit postpartum weight retention.